PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN PADA BENGKEL MEMORY AUTO SERVICE DI KECAMATAN JEUNIEB KABUPATEN BIREUEN - MUKHLISIN ZAKARIA SAKDIYAH (Jurnal Economica Didactica, 2020)
ABSTRACTThis research entitled "The Effect of Service Quality on Customer Loyalty in Memory Auto Service Workshop atKecamatan Jeunieb Kabupaten Bireuen". The aims of this study are to determine service quality and customer loyalty in the Memory Auto Service Workshop atKecamatan Jeunieb Kabupaten Bireuenand to determine the effect of service quality on customer loyalty at the Memory Auto Service Workshop at Kecamatan Jeunieb Kabupaten Bireuen. This study uses a descriptive method with a quantitative approach. The population in this study were all customers who used the doorsmeer services at the Memory Auto Service Workshop atKecamatan Jeunieb Kabupaten Bireuen with more than 423 customers. The sample in this study were 63 customers or 15% of the population. The sampling technique in this study was incidental sampling technique. While the techniques used in data collection were library research and field research through questionnaires and documentation. The data analysis techniques used were simple linear regression, correlation coefficient and determination, and t test to prove the research hypothesis. Based on the results of data analysis obtained the results of correlation studies found r = 0.506 which means the correlation between service quality variable with customer loyaltyvariable is sufficient. The coefficient of determination result shows the effect of service quality on customer loyalty is 0.711 or 71.1%. Furthermore, the t test on the significance level of 5% hypothesis is accepted, as evidenced from the value of tcount = 7.904 ttable (0.05, 61) = 1.999. The conclusion of this study is that there is an effect between service quality and customer loyalty. If the quality of service is given well it will create customer satisfaction which will ultimately create customer loyalty.